Dupilumab-associated facial redness not responsive to antifungal therapy successfully treated with tralokinumab - Ambrosio, Luca; Tolino, Ersilia; Proietti, Ilaria; Bernardini, Nicoletta; Skroza, Nevena; Potenza, Concetta (Acta Biomedica Atenei Parmensis, 2024)
Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by eczematous lesions and intense itching. Dupilumab, was the first biological drugs approved for this disease. Dupilumab-associated facial redness (DFR), characterized by facial and/or neck erythema, was never reported during pivotal clinical trials. It has been observed in 4-10% of patients treated with dupilumab in real-life settings.A twenty-one-year-old male developed non-pruritic erythematous patches in the frontal, palpebral, malar, latero-cervical, and nuchal areas after about eight weeks of treatment with Dupilumab. Since the patient did not perform patch test before starting dupilumab, to rule out possible allergic contact dermatitis (ACD), patch tests were performed using standard and personal product series pediatric series, which yielded negative results. A skin scraping and a microscopic examination with negative result were performed in order to rule out possible Demodicosis and head and neck dermatitis due to Malassezia species. After conducting a literature review, it was decided to discontinue Dupilumab and start fluconazole therapy. However, this approach did not significantly improve the EASI score for the head/neck region. Due to the negative impact that the Dupilumab therapy-related manifestation had on the patient’s quality of life, a decision was made to switch to Tralokinumab. This treatment resulted in the resolution of DFR after only three administrations while maintaining excellent disease control. Tralokinumab also demonstrated an excellent safety profile even after sixteen weeks of treatment. This paper presents what could be the first case of DFR to be successfully treated with Tralokinumab.